Imaging and Analysis of Presynaptic Calcium Influx in Cultured Neurons Using synGCaMP6f - Brockhaus, Johannes; Brüggen, Bianca; Missler, Markus (Frontiers in Synaptic Neuroscience, 2019)
Presynaptic Ca2+ influx through voltage-gated calcium channels (VGCCs) is a key step in synaptic transmission that links action potential-derived depolarization to vesicle release. However, investigation of presynaptic Ca2+ influx by patch clamp recordings is difficult due to the small size of the majority of synaptic boutons along thin axons that hamper clamp control. Genetically encoded calcium indicators (GECI) in combination with live cell imaging provide an alternative method to study Ca2+ transients in individual presynaptic terminals. The indicator GCaMP6f was developed for fast speed and high sensitivity in detecting Ca2+ transients even in subcellular compartments. We conjugated GCaMP6f to synaptophysin (synGCaMP6f) to enrich the calcium indicator in presynaptic boutons of transfected primary hippocampal neurons to study presynaptic Ca2+ changes in response to individual action potentials (AP) or short bursts. Changes in fluorescence intensity were evaluated by normalization to control level or, alternatively, by normalization to maximal fluorescence using the calcium ionophore ionomycin. Measurements revealed robust Ca2+ transients with amplitudes that depend on parameters like the number of APs, stimulation frequency or external calcium concentration. Our findings indicate an appropriate sensitivity of synGCaMP6f for studying total presynaptic Ca2+ transients induced by single APs or short bursts that showed little rundown of the response after repeated bursts. Moreover, these recordings are fast enough to even study short-term plasticity like paired pulse facilitation and frequency dependence of Ca2+ transients. In addition, synGCaMP6f could be used to dissect the contribution of different subtypes of VGCCs to presynaptic Ca2+ influx. Our results demonstrate that synGCaMP6f allows the reliable analysis of changes in presynaptic calcium concentration at many individual synaptic boutons in parallel and provides the possibility to study the regulation of this important step in synaptic transmission.